Massive Ice Control on Permafrost Coast Erosion and Sensitivity. Issue 17 (31st August 2020) - Lim, M.; Whalen, D.; Martin, J.; Mann, P. J.; Hayes, S.; Fraser, P.; Berry, H. B.; Ouellette, D.
Abstract: High overall rates of permafrost cliff retreat, coupled with spatial variability, have been accompanied by increased uncertainty over future landscape dynamics. We map long‐term (>80 years) retreat of the shoreline and photogrammetrically analyze historic aerial imagery to quantify the processes at a permafrost coast site with massive ground ice. Retreat rates have been relatively constant, but topographic changes show that subsidence is a potentially critical but often ignored component of coastal sensitivity, exceeding landward recession by over three times during the last 24 years. We calibrate novel passive seismic surveys along clear and variable exposures of massive ground ice and then spatially map key subsurface layers. Combining decadal patterns of volumetric change with new ground ice variation maps enables past trends to be interpreted, future volumetric geomorphic behavior to be better constrained, and improves the assessment of permafrost coast sensitivity and the release of carbon‐bearing material. Plain Language Summary: Arctic coasts are eroding faster than other coasts, in part because they contain ground ice and frozen material that is particularly sensitive to changes in temperature and the many associated processes it influences. These high erosion rates threaten coastal communities, infrastructure, and habitats, but understanding future patterns of change is complicated by the often unpredictable presence of ground ice located within coastal material and how it is responding over time. Here we examine a site on the Beaufort Sea coast where there are known large exposures of this ground ice. We used historic images to create a 3‐D model of past land surface heights to calculate changes over time. These changes show large‐scale lowering of the land surface over recent decades, in addition to the erosion of the coast. We then apply a new ground measurement approach to map where the ice remains. These new data are vital for understanding both future erosion processes and the subsequent release of climatically important gases and material. Key Points: The volumetric change at a massive ice site associated with subsidence was over 3 times greater than coastal erosion since 1994 Passive seismic surveys have been used to map current massive ice distribution across the site in the context of these landscape dynamics Accounting for massive ice presence and sensitivity improves forecasts of permafrost coast erosion and inferences of carbon release rates